Contribution of Manufacturing Industry, Agribusiness Industry, Marine Industry Through People’s Welfare to Economic Growth in Batam, Indonesia - Wibisono, Chablullah; ., . (International Journal of Engineering and Technology, 2018)
Since 1972 the island of Batam designated as the industry, trade, tourism and over the ship. since it is located close to Singapore so that industry in Batam only manufacture, but in the development of all the mostly consumed comes from outside (import) and the broad sea area ofÂ 715 square km total area of 1,575 square kilometers along the sea. This study aims to know Contributions Industrial Manufacturing, Agribusiness Industry, Marine Industry Against Public Welfare Through Economic Growth Batam. In this study sampled is Indonesian Chamber were 200 respondents. The results of analysis by using SEM* assisted AMOS* Software version 22, Square Multiple Correlation. Thus it can be stated that the change of Economic Growth by contributions from the Industrial Manufacturing, Agribusiness Industry, Marine Industry 56.7%. Tus it can be stated that the People's Welfare changes by contributions from the Industrial Manufacturing, Agribusiness Industry, Marine Industry and Economic Growth of 56.7%. From this research, it is interesting to conclude: that manufacturing contributes Significantly to economic growth, but not to the people's welfare, while agribusiness and marine contribution members of the economic growth are not significant, but it Gives the agribusiness and marine public welfare significant contribution,Â Â